Patient Outcomes After Revision of Anatomic Total Shoulder Arthroplasty to Reverse Shoulder Arthroplasty for Rotator Cuff Failure or Component Loosening: A Matched Cohort Study. Issue 4 (15th February 2019) - Shields, Edward; Wiater, J. Michael
Abstract : Purpose: To compare outcomes after conversion of anatomic total shoulder arthroplasty (aTSA) to reverse total shoulder arthroplasty (RTSA) and a matched cohort. Methods: Patients converted from aTSA to RTSA for rotator cuff failure or component loosening and a primary RTSA matched cohort were retrospectively identified from a prospective database. Demographics and preoperative and postoperative outcomes were obtained and compared. Results: Age, sex, body mass index, follow-up length, and preoperative function were similar between revision (n = 35) and primary (n = 70) groups. At final follow-up, visual analog scale pain (2.4 ± 2.8 versus 1.7 ± 2.8; P = 0.24) and American Shoulder and Elbow Surgeons (68 ± 26 versus 76 ± 24; P = 0.14) scores were similar. The revision group had worse subjective shoulder value scores (63 ± 30 versus 79 ± 21; P = 0.002), satisfaction (74% versus 90%; P = 0.03), and more complications (31% versus 13%; P = 0.02). Conclusion: Revision of aTSA to RTSA for component loosening or rotator cuff failure results in function comparable to primary RTSA; however, more complications, worse subjective shoulder value scores, and lower patient satisfaction should be expected. Level of Evidence: Level III, retrospective comparative